Draft Annual Plan, 2003-04 Volume I (Part-II) Government of Uttar Pradesh - Planning Commission (Planning Commission, 2003)
The economy of the state is primarily agrarian, where 75% the workforce earns its livelihood from agriculture. the share of agriculture sector in the total state income is about 36 percent. One of the most fertile tracts in the world is the Gangetic plain and Uttar Pradesh covers half of it. Uttar Pradesh can easily be called the country’s agricultural heartland and has plenty of rich alluvial soils and abundant ground and surface water. on account of variety of soils and climatic conditions, the state has nine distinct agro-climatic zones which show variation in productivity of various types of food crops.
Government of Uttar Pradesh, State Planning Commission